Comparing endocervical mucus proteome of humans and rhesus macaques. Issue 4 (26th May 2021) - Han, Leo; Park, Daye; Reddy, Ashok; Wilmarth, Phillip A.; Jensen, Jeffrey T.
Abstract: Purpose: Endocervical mucus changes play a key role in regulating fertility throughout the menstrual cycle and in response to hormonal contraceptives. Non‐human primates (NHP) provide the most translational animal model for reproductive tract studies, as they have hormonally‐regulated menstrual cycles and mucus changes, similar to women. Experimental Design: We used TMT labelling and LC‐LC/MS to compare the proteins found in the mucus of the rhesus macaque to the mucus of the human endocervix. Data are available via ProteomeXchange with identifier PXD021710. Results: We found 3048 total proteins present in both rhesus mucus and human mucus, and of these, 57% showed a similar expression pattern. An even higher similarity occurred in the top 500 most prevalent proteins, with overlap in 341 (68%) proteins. Mucin MUC5B was the most highly expressed mucin protein (top 10 expressed proteins in both) but other key proteins related to mucus structure were present in both samples. Conclusions and Clinical Relevance: We find that the mucus proteome of the endocervical mucus is highly conserved in NHP and women. This supports use of the NHP model system for studies of the endocervix and trials of novel fertility treatments targeting the cervix.